Avoided Deforestation Linked to Environmental Registration of Properties in the Brazilian Amazon. Issue 3 (27th October 2017) - Alix‐Garcia, Jennifer; Rausch, Lisa L.; L'Roe, Jessica; Gibbs, Holly K.; Munger, Jacob
Abstract: We quantified the avoided deforestation impacts of environmental land registration in Brazil's Amazonian states of Mato Grosso and Pará between 2005 and 2014. We find that the program reduced deforestation on registered lands. The magnitude of the effect implies that deforestation in the two states would have been 10% higher in the absence of the program. The impacts of registration varied over time, likely due to changing suites of policies linking environmental registration to land use incentives. Our results also reveal that agriculturally suitable lands and those located in regions undergoing the most land‐use change were more likely to be registered than those in less suitable, less dynamic regions. We conclude that environmental registration is an important first step in implementing avoided deforestation policies targeting private landholders.